Population, economic and geographic predictors of nations' medal tallies at the Pyeongchang and Tokyo Olympics and Paralympics - Li, F.; Hopkins, W. G.; Lipinska, P. (Frontiers in Sports and Active Living, 2022)
Purpose: Ranking of nations by medal tally is a popular feature of the Olympics, but such ranking is a poor measure of sporting prowess or engagement until the tallies are adjusted for major factors beyond the control of individual nations. Here we estimate and adjust for effects of total population, economy expressed as gross domestic product per capita, absolute latitude and Muslim population proportion on total medal counts in female, male, mixed and all events at the Pyeongchang winter and Tokyo summer Olympics and Paralympics.